Who cares for the suffering other? A survey-based study into reactions toward images of distant suffering. (October 2019) - Huiberts, Eline; Joye, Stijn
A growing number of scholars have empirically engaged with audience reactions toward mediated distant suffering, albeit mainly on a small, qualitative scale. By conducting quantitative research, this study contributes to the knowledge about people's reactions toward distant suffering on a greater scale, representative of a Western audience. Following a critical realist approach, a survey was developed and several independent constructs were found by doing an exploratory factor analysis which represents people's engagement with distant suffering. We also found four clusters based on a k-means cluster analysis that portrays typical ways of responding to distant suffering. These clusters have been controlled for people's background, indicators of age, gender, education and people's donation behavior, media use, and news interests.